Macroglossia : A Case Report - NP, Nataraja; PJ, Kumar (Journal of All India Institute of Speech and Hearing)
This paper is a report on a case of Macroglossia.The articulatory behaviour of a boy of 14 years with a congenital cystic swelling occupying the anterior 1/3 of the tongue approximately 50 c.c.) has been described.